Evaluating the Behavior of Embankments after Widening considering Soil Consolidation and Splicing Mode - Xiaobo Xing; Zhenhao Bao; Wei Li (Advances in Civil Engineering)
Increased traffic volume has made it necessary to increase highway capacities by widening embankments and pavements. Differential settlement of foundation consolidation and rational utilization of existing embankments are the main problems encountered in road reconstruction. In this paper, the finite difference method is used to simulate the construction process of using the existing embankments directly in the reconstruction project of expressway, and the fluid-solid coupling model of foundation settlement is established to calculate the differential settlement between foundation and subgrade. The influence of road widening mode and embankment height on differential settlement is analyzed. The mechanical response of subgrade under differential settlement is simulated and the law of uneven settlement of main reconstruction forms is investigated. The dynamic response of existing embankments soil under the action of rammer is systematically evaluated. The results show that, with the increase of consolidation time, the differential settlement is gradually obvious at the junction of the new and existing embankments, and there is a possibility of landslide along the junction of new embankments, which should be dealt with in engineering. The smaller the height difference between the existing foundation and the new foundation is, the more the position of the maximum settlement point of the foundation moves towards the new foundation. The greater the height of the new subgrade is, the greater the uneven settlement is. The criterion based on the single rammed energy and compaction stopping standard is proposed to determine the reinforcement depth of existing embankment.